‘Transplanting Hope’: Experimental Stem Cell Therapy and the Political Economy of an HIV Cure - Kris Herik de Oliveira (Vibrant: Virtual Brazilian Anthropology)
Abstract In this article, I use a socio-anthropological perspective to analyze the configurations and developments of the first five cases of an HIV “cure” or “long-term remission”. These unprecedented results in the history of medicine were achieved through experimental stem cell transplants, whose donors had a rare genetic mutation called CCR5Δ32/Δ32, which confers a “natural resistance” to HIV infection. More specifically, I seek to explore the role of hope in these assemblages, that is, how it is manifest in narratives and composes situated practices. To do so, I collected and analyzed the content of scientific, journalistic, and biographical documents in a cartographic exercise (2008-2023). I observed that the first “success stories” in curative therapies for HIV can be seen as events in the trajectory of the HIV/AIDS pandemic that promoted short-circuits in the status quo and sparked new techno-scientific controversies. In this context, hope reveals complex and fluid connections, mobilizes desires, creates possibilities, attracts investments, and fosters discourses about the supposed “end” of the HIV/AIDS pandemic. Finally, I suggest that this reflection is situated within a broader technobiopolitical network, which I call the “political economy of the HIV cure”.